1981
DOI: 10.1042/bj1990081
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical analysis of cartilage proteoglycans. Cross-reactivity of molecules isolated from different species

Abstract: Antibodies directed against whole bovine nasal-cartilage proteoglycan and against the hyaluronic acid-binding region and chondroitin sulphate peptides from the same molecule were used in immunodiffusion and immunoelectromigration experiments. Proteoglycans from bovine nasal and tracheal cartilage showed immunological identity, with all three antisera. Proteoglycans from pig hip articular cartilage, dog hip articular cartilage, human tarsal articular cartilage and rat chondrosarcoma reacted with all the antiser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Comparison of the results indicates that the binding regions of cow (89%) and dog (78%) show a high degree of cross-reactivity with that of pig, with rat (37%) and human (22%) giving lower values and with rabbit (15%) being the lowest. Comparable results for antisera to proteoglycans from bovine nasal cartilage have been reported by Wieslander & Heinegard (1981). Discussion…”
Section: Fig 1 Titration Of (A) Anti-(link Protein) Antiserum and (supporting
confidence: 72%
“…Comparison of the results indicates that the binding regions of cow (89%) and dog (78%) show a high degree of cross-reactivity with that of pig, with rat (37%) and human (22%) giving lower values and with rabbit (15%) being the lowest. Comparable results for antisera to proteoglycans from bovine nasal cartilage have been reported by Wieslander & Heinegard (1981). Discussion…”
Section: Fig 1 Titration Of (A) Anti-(link Protein) Antiserum and (supporting
confidence: 72%
“…Furthermore, Triphaus et al (1980) found two metabolically distinct populations of proteoglycans in human xiphoid cartilage. Immunochemical studies indicated that cartilage extracts contain more than one population of proteoglycans (Wieslander & Heinegard, 1981), and in the present study we have purified two antigenically distinct populations of aggregating proteoglycans.…”
Section: Discussionmentioning
confidence: 53%
“…The large proteoglycan synthesized by arterial smooth muscle cells resembles the large proteoglycan population recently isolated from human aorta by Salisbury and Wagner (6) The smaller proteoglycan present in the medium contains dermatan sulfate. To some extent, this population resembles the small "ubiquitous" component produced by other mesenchymal ceils in vitro (49,50,52,53) and that recently isolated and characterized from cartilage (54). Several investigators have noticed the presence of dermatan sulfate proteoglycans in various tissue (55)(56)(57)(58)(59) including aorta (1,3,4,5,55).…”
Section: Discussionmentioning
confidence: 83%